Analisis Bukti Retorika Pidato Nadiem Makarim pada Hari Guru Nasional 2019 - Atika Try Harini Isa (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
The rhetoric theory is a communication theory that has been used since Ancient Greek. Aristotle was the first theorist who considered rhetoric as an art & studied rhetorics in a serious manner. According to Aristotle, rhetoric is the discovery of the available means of persuasion in every way. Rhetoric is a proof or indication of whether a speaker is great at executing persuasive messages in every form such as speech, message, or text. One of the most important concepts in rhetoric is rhetorical proof by Aristoteles. There are two kinds of rhetorical proofs, artistic & non-artistic proof. These proofs according to Aristotle are divided into three forms, ethos or ethical proof is the speaker’s credibility, pathos or emotional proof is the speaker’s emotion that showed, & logos or logic proof is an argumentation or rationalization which made sense to the audience. A good speaker is someone who uses all three of the artistic rhetorical proofs when speaking. This study aimed to analyze the artistic rhetorical proofs in the speech of The Minister of Education & Culture of Indonesian Republic on The National Teacher’s Day 2019. This study also aimed to complete the previous study which only discussed the five canons of the rhetoric of this speech. The method used in this study was qualitative descriptive, by analyzed the artistic rhetorical proofs of the speech of Republic Indonesia’s Minister of & goodwill, pathos by showing admiration, indignation, friendliness, confidence and anger, and logos in both of its forms, enthymeme, and example.